2021
DOI: 10.1177/20420188211066210
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome is associated with prostate enlargement: a systematic review, meta-analysis, and meta-regression on patients with lower urinary tract symptom factors

Abstract: Background: Metabolic syndrome (MetS) is defined by at least three of the following five criteria: blood pressure ⩾130/85 mmHg, fasting blood glucose ⩾5.6 mmol/l, triglycerides concentration ⩾1.7 mmol/l, waist circumference ⩾102 cm (for men), and high-density lipoprotein cholesterol concentration <1.03 mmol/l (for men). MetS has been associated with worse lower urinary tract symptoms (LUTS) and higher International Prostate Symptom questionnaire scores. Materials and Methods: MEDLINE, Cochrane, ClinicalTria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…In contrast to women from the CARDIA cohort study, we did not find associations of cardiovascular risk factors with LUTS/impact clusters in men 9 . Cardiovascular risk factors are associated with LUTS in men in other cohort studies 13,14,23–26 . The present study combined self‐reported symptoms and impact on QoL to create an index of bladder health.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In contrast to women from the CARDIA cohort study, we did not find associations of cardiovascular risk factors with LUTS/impact clusters in men 9 . Cardiovascular risk factors are associated with LUTS in men in other cohort studies 13,14,23–26 . The present study combined self‐reported symptoms and impact on QoL to create an index of bladder health.…”
Section: Discussionmentioning
confidence: 60%
“…The newer definition of cardiovascular health includes the presence of both ideal health behaviors (nonsmoking, body mass index < 25 kg/m 2 , physical activity at goal levels, and pursuit of a diet consistent with current guideline recommendations) and ideal health factors (untreated total cholesterol < 200 mg/dL, untreated blood pressure <120/<80 mmHg, and fasting blood glucose < 100 mg/dL), as well as getting adequate sleep 12,27 . In a recent systematic review of metabolic syndrome and LUTS in men, the authors concluded that good evidence existed to support a relationship between metabolic syndrome and prostatic enlargement, but not for LUTS 26 . Only 7% of the men in CARDIA (average age 50 ± 3.6 years) reported having a diagnosis of prostate enlargement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower levels of observed PSA in overweight men compared with normal-weight men may also account for some of the observed inverse association between overweight and metastatic PCa. On the other hand, obesity and metabolic syndrome have been associated with lower urinary tract symptoms (LUTS) [46,47], which may entail a more widespread use of PSA-testing, thus increasing the probability of being diagnosed with PCa at an earlier stage. Even so, the degree of LUTS have not been found to correlate with PCa [48,49].…”
Section: Discussionmentioning
confidence: 99%